Коливання врожаїв томатів в Україні - Ярмольська, О.Є. (Культура народов Причерноморья, 2013)
Проведена оцінка мінливості врожаїв томатів в різних кліматичних зонах України, яка
відображає особливості термічного режиму та режиму забезпечення вологою кожного конкретного
року. Досліджені рівні коливання врожаїв томатів в Україні, їх динаміка, побудовані лінії трендів.
Підвищення врожаїв томатів можливе за рахунок багатьох факторів: введення у виробництво нових,
більш продуктивних сортів, введення сортового районування, при якому розміщення різних за
скоростиглістю сортів виконується з врахуванням відповідності агрокліматичних ресурсів території
біологічним особливостям цих культур. Можно зробити висновок, що культура томатів в областях
Південного Степу відзначається найвищою дохідністю. Проведена оценка изменчивости урожаев томатов в разных климатических зонах
Украины, которая отражает особенности термического режима и режима обеспеченности влагой
каждого конкретного года. Исследованы уровни колебания урожаев томатов в Украине, их динамика,
линии трендов. Повышение урожайности томатов возможно за счет многих факторов: введения в
производство новых, более продуктивных сортов, введение сортового районирования, при котором
размещение разных по скороспелости сортов выполняется с учетом соответствия агроклиматических
ресурсов территорииї биологическим особенностям этих культур. Можно сделать вывод, что
культура томатов в областях Южной Степи определяется наибольшой доходностью. The assessment of changes of the harvests of tomatoes in the different climatic areas of Ukraine is
shown, which highlights the special features of the thermal regime and water supply regime for an each
particular year. The limited oscillation of the harvest of tomatos in Ukraine, its dynamix, trends lines are
researched.
The increasing of the productivity of tomatoes is possible with many ways: introduction into production of new,
more effective grades, application of the grades zoning, when placing of the grades with different precocity is
being carried out taking into account the compliance of local agro climatic resources to biological features of
given plants. The conclusion is, that cultivation of tomatoes in the Southern Steppe region is highly profitable.
The productivity of tomatoes cultivation differs throughout Ukraine. In the Forest Area it is ranged at 50
through 125 c/h, in the Forest/Steppe Area it is ranged at 58 through 208 c/h, Northern Steppe Area it is
ranged at 150 through 300 c/h, in Southern Steppe Area it is ranged at 173 through 458 c/h. Like others
cultivated vegetable, the tomatoes productivity trend oscillates as in time , as in area. The dynamic graphs of the
tomatoes harvesting throughout different climatic zones in Ukraine are introduced along with estimation of
trend lines. There are yearly deviation out of harvesting trend lines.